(untitled) (JPK : Jurnal Proteksi Kesehatan, 2022)
Staphylococcus aureus is a bacterium that can cause several diseases in humans such as ulcers and wound infections. Matoa leaves contain phenolic and flavonoid compounds which are known to have antibacterial properties. The purpose of this study was to determine the antibacterial activity of the ethanolic extract of Pometia pinnata J.R. & G.Forst leaves against Staphylococcus aureus at concentrations of 10%, 20%, and 30%. This research was conducted by disc diffusion method on Mueller Hinton Agar (MHA) media. Antibacterial activity was measured by looking at the inhibition of the growth of S. aureus bacteria. Based on the results of the study, it was found that the ethanolic extract of matoa leaves was able to inhibit the growth of S. aureu bacteria with the average inhibition zones produced at concentrations of 10%, 20% and 30%, namely 11.06 mm, 15.07 mm, 16.07 mm and control ciprofloxacin positive was 28.10 mm. From the results above, it can be concluded that the ethanolic extract of matoa (Pometia pinnata) leaves has antibacterial activity against Staphylococcus aureus.